2017
DOI: 10.3389/fphys.2017.00019
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Brain 1H-MR Glutamine and Glutamate Signals Following Acute Exhaustive Endurance Exercise in the Rat

Abstract: Objective: Proton magnetic resonance spectroscopy (1H-MRS) in ultra-high magnetic field can be used for non-invasive quantitative assessment of brain glutamate (Glu) and glutamine (Gln) in vivo. Glu, the main excitatory neurotransmitter in the central nervous system, is efficiently recycled between synapses and presynaptic terminals through Glu-Gln cycle which involves glutamine synthase confined to astrocytes, and uses 60–80% of energy in the resting human and rat brain. During voluntary or involuntary exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Interestingly, a 7T MRS study in which rats were exercised to exhaustion revealed greater increases in glutamine relative to glutamate (Swiatkiewicz et al . ). Nonetheless, we note that Dennis et al .…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, a 7T MRS study in which rats were exercised to exhaustion revealed greater increases in glutamine relative to glutamate (Swiatkiewicz et al . ). Nonetheless, we note that Dennis et al .…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Guezennec et al ( 1998 ) reported the Glu level was reduced after exhaustion in the striatum of rats. Świątkiewicz et al ( 2017 ) using proton magnetic resonance spectroscopy technique showed that the Glu signal was increased in the cerebellum and hippocampus, but not changed in the striatum of rats following acute exhaustive exercise. However, Liu et al ( 2011 ) reported that the content of Glu was significantly increased in rat’s telencephalon after EF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the population (fewer studies in young adults) and potential temporal effects of exercise on memory, three additional gaps in the literature include the exercise stimulus, memory type, and memory follow‐up period. With regard to the exercise stimulus, and despite animal work demonstrating that high‐intensity exercise is effective in increasing post‐synaptic excitatory activity (Swiatkiewicz et al ., ) and long‐term memory (Wang & Wang, ), the majority of research in the young adult population (Miles & Hardman, ; Libkuman et al ., ; Covassin et al ., ; Sibley & Beilock, ; Labban & Etnier, ; Berman et al ., ; Gothe et al ., ; Nanda et al ., ; Basso et al ., ; Loprinzi & Kane, ; McNerney & Radvansky, ; Bantoft et al ., ; Hwang et al ., ) has employed moderate‐intensity exercise protocols. Regarding memory type, all of the studies in the young adult population (Miles & Hardman, ; Libkuman et al ., ; Covassin et al ., ; Sibley & Beilock, ; Labban & Etnier, ; Berman et al ., ; Gothe et al ., ; Nanda et al ., ; Basso et al ., ; Loprinzi & Kane, ; McNerney & Radvansky, ; Bantoft et al ., ; Hwang et al ., ) have examined either retrospective‐related episodic memory, recognition memory, logical memory, working memory, long‐term memory, visuospatial memory, or verbal memory.…”
Section: Introductionmentioning
confidence: 99%